Karakterisasi Morfologi Phytophthora sp. Asal Buah Kakao Desa Olo-oloho, Kabupaten Konawe, Sulawesi Tenggara - Muzuni Muzuni; Haidin Haidin; Nur Arfa Yanti (University of Halu Oleo, 2020)
This study aimed to determine the morphological characteristics of Phytophthora sp. isolated from cocoa fruits from Olo-oloho Village, Konawe Regency, Southeast Sulawesi. Isolation of Phytophthora sp. carried out by the point method using V4 (Vegetable Juice Agar) media incubated at 27ºC for 24 hours. Morphological characterization of Phytophthora sp. included characterization of colony morphology and cell morphology. The results showed that the colony morphological characteristics were white colonies, cotton-like textures, the uneven edge of the colony, zoning and radial lines. The morphological characteristics of the cell had asexual spores in the form of sporangium and chlamydospores, hyphae are not aseptic, greenish-black zoospores, zoospores are round and double-flagged, and have sporangiophores. Keywords: Phytophthora sp., colony morphology, cell morphology